Mrs-preemie model: innovative nursing intervention to improve maternal and preterm infant outcomes - Nopi Nur Khasanah; Yeni Rustina; Dessie Wanda; Sutanto Priyo Hastono; Iskim Luthfa (Pediomaternal Nursing Journal, 2026)
Introduction: Mothers of preterm infants are particularly susceptible to emotional distress, which may impair bonding and hinder optimal infant growth. Nurses hold a critical position in supporting both maternal and infant outcomes through structured interventions. Objective: This study aimed to evaluate the effectiveness of the Mrs-Preemie model, an innovative nursing intervention, on reducing maternal stress, enhancing mother-infant bonding, and improving weight gain in preterm infants. Methods: A mixed-methods exploratory sequential design was employed, using purposive sampling. The qualitative phase involved 24 mothers and 13 nurses to identify care needs, followed by expert panel validation with four professionals. In the quantitative phase, 66 mother-father-preterm infant triads participated. The intervention group received the Mrs Preemie model, which comprised four modules implemented over four weeks; the control group received standard care. Outcomes included maternal stress and bonding scores, and infant weight, assessed at baseline, week two, and week four. Confounding variables were statistically controlled. Results: Thirteen themes emerged to guide the model's development. Statistically significant differences were found between the intervention and control groups over time for maternal stress (P-value=.001), mother-infant bonding (P-value=.001), and infant weight (P-value=.013). After four weeks, the intervention group showed significantly reduced maternal stress (P-value<.001), improved bonding (P-value=.002), and greater infant weight gain (P-value<.001). Improvements in maternal outcomes emerged by week two, while infant weight gain was evident by week four. Conclusion: The Mrs-Preemie model demonstrates effectiveness as an innovative nursing intervention to improve maternal psychological well-being and preterm infant development. Integrating it into neonatal nursing is recommended. Keywords: mother-child relations; premature infants; psychological stress; weight gain